Judicial affairs: history, moral development, and the critical role of students - Krapfl, Kristen A. (Kansas State University, 2011)
Judicial affairs play an integral role in the functioning of an institution and in the moral development of students. Thus, it is critical to have an understanding of the structures that are utilized, how to choose the most effective structure for one’s specific institution, and how to successfully bring about the moral and ethical development of students. The purpose of this report is to examine the judicial structures that are in place at institutions of higher education and their impact on students. Topics discussed include the history of discipline and current judicial structures that are commonly utilized (e.g., legalistic, collaborative, honor codes, and restorative justice), how they function, and if an ideal judicial structure exists. In addition, the report addresses the theoretical foundations of moral and ethical development through the work of Gilligan (1982), Kohlberg (1964), Perry (1981), and Piaget (1965), and provides perspectives and insight on the judicial process from both judicial and student affairs administrators as well as students who have experienced the process. The findings presented in the report include the transition from judicial systems run by administrators to those run primarily by students, and the importance of understanding theories of student moral development despite the process that is chosen. Also noted are the significant impact of a student’s moral development on their perceptions of the process and on their resultant behaviors, and the role the campus environment plays in regards to behavior and discipline. Additionally, the findings convey the importance of employing judicial structures that are effective for the student population at the institution, and not subscribing to a one-size-fits-all model. Finally, the crucial role of evaluation and continual improvement in creating an effective structure, and the implications for future practice that come from this are discussed.
Keywords: Judicial affairs; Discipline; Moral development; Higher Education (0745); Higher Education Administration (0446)